2016
DOI: 10.1186/s12939-016-0320-1
|View full text |Cite
|
Sign up to set email alerts
|

Why are the poor less covered in Ghana’s national health insurance? A critical analysis of policy and practice

Abstract: BackgroundThe National Health Insurance Scheme (NHIS) was introduced in Ghana to ensure equity in healthcare access. Presently, some low and middle income countries including Ghana are using social health insurance schemes to reduce inequity in access to healthcare. In Ghana, the NHIS was introduced to address the problem of inequity in healthcare access in a period that was characterised by user-fee regimes. The premium is heavily subsidised and exemption provided for the poorest, yet studies reveal that they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 26 publications
9
56
0
Order By: Relevance
“…This finding seems to contradict the postulated hypothesis that the newly introduced public insurance scheme will provide more coverage for women of low socioeconomic status than for their well‐off counterparts, and challenges the underlying assumption that the insurance scheme will foster healthcare access equity. In agreement with the present results, studies conducted in Ghana showed less national health insurance coverage among the poor. The disparity in insurance coverage by wealth status indicates that Togo is lagging in addressing the importance of insurance in protecting against health‐related financial risks among the poor.…”
Section: Discussionsupporting
confidence: 93%
“…This finding seems to contradict the postulated hypothesis that the newly introduced public insurance scheme will provide more coverage for women of low socioeconomic status than for their well‐off counterparts, and challenges the underlying assumption that the insurance scheme will foster healthcare access equity. In agreement with the present results, studies conducted in Ghana showed less national health insurance coverage among the poor. The disparity in insurance coverage by wealth status indicates that Togo is lagging in addressing the importance of insurance in protecting against health‐related financial risks among the poor.…”
Section: Discussionsupporting
confidence: 93%
“…This is especially so due to the fact that the law requires that the poor who will qualify for premium exemption be homeless. In the extended family culture of Ghana, homelessness almost does not exist as the very poor normally live in family houses, with friends, or in dilapidated houses …”
Section: Resultsmentioning
confidence: 99%
“…Despite the insurance enrolment camps, heavy subsidisation, and exemptions from contributions, the poor are still at least twice less likely to be enrolled in Ghana's NHIS than the rich. 162 This is partially due to policy incoherence e.g. one of the stipulated criteria to identify the core poor is not having a fixed place of residence, which is only rarely the case and in effect disqualifies many of the poor.…”
Section: Panel 4: Examples Of Health Insurance In Ghana Rwanda and Smentioning
confidence: 99%